2021
DOI: 10.3390/rel12030145
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Resonance of Official Islam in Oman, Jordan, and Morocco

Abstract: Acts of political violence carried out by Muslim individuals has generated international support for governments that espouse so-called “moderate Islam” as a means of preventing terrorism. Governments also face domestic skepticism about moderate Islam, especially if the alteration of official Islam is seen as resulting from external pressure. By evaluating the views of individuals that disseminate the state’s preferred interpretation of Islam—members of the religious and educational bureaucracy—this research a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
1
1
Order By: Relevance
“…Speakers consider the importance of the unity of Arab countries to overcome the occupation experienced by the Palestinian people. It is different from the findings of (Al Zidjaly, 2010;Culpeper et al, 2017;Sheline, 2021) which revealed the context of religious identity in impoliteness speech on social media. Thus, research findings will contribute to the development of theories and studies of language impoliteness (Haugh, 2018).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Speakers consider the importance of the unity of Arab countries to overcome the occupation experienced by the Palestinian people. It is different from the findings of (Al Zidjaly, 2010;Culpeper et al, 2017;Sheline, 2021) which revealed the context of religious identity in impoliteness speech on social media. Thus, research findings will contribute to the development of theories and studies of language impoliteness (Haugh, 2018).…”
Section: Discussioncontrasting
confidence: 99%
“…The study draws on Spencer-Oatey (2007 where Arabic Youtube user comments are dominated by impolite language. From the aspect of the object, this study focuses on discussing the Palestinian conflict, while previous studies discuss conflicts in other Arab countries (Badarneh & Migdadi, 2018;El-Falaky, 2019;Gordon et al, 2017;Harlow, 2012;Labben, 2018;Sheline, 2021;Sinatora, 2019).…”
Section: Introductionmentioning
confidence: 99%